Albinism in larvae of the Chacoan frog Leptodactylus chaquensis (Anura, Leptodactylidae) from an urban lake from Argentina - Martinuzzi, Candela Soledad (2016)
We report complete albinism in Leptodactylus chaquensis (Cei, 1950; Amphibia, Anura) larvae. Two foam nests were collected from an urban lake and maintained in outdoor tanks during metamorphosis. Different proportions of albino larvae and metamorphs occurred. This is the first observation of several larvae of L. chaquensis with albinisms from an urban lake with continuous artificial and natural luminosity.